Quality of Life and Level of Physical Activity In Students with and without Symptoms of Functional Dyspepsia and Irritable Bowel Syndrome Surveyed with Questionnaire “7×7” (7 Symptoms Per 7 Days) - T. V. Zhestkova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. Assessment of the quality of life and physical activity level in students with and without symptoms of functional dyspepsia (FD) and irritable bowel syndrome (IBS) according to questionnaire “7×7” (7 symptoms per 7 days).Materials and methods. Symptoms of FD and IBS were surveyed using the “7×7” questionnaire. Level of physical activity was evaluated according to the short IPAQ, and quality of life — to WAM questionnaires.Results. The study surveyed 92 students aged 20.7 ± 0.2 years (56 men and 36 women). We report borderline manifestations of functional disorders of the gastrointestinal tract (GIT) in 51.1 %, and FD and/or IBS symptoms of mild to moderate severity in 23.9 % of respondents. Symptoms of FD and/or IBS were equally common in men and women. Severity of FD and/or IBS symptoms was rated 4 [[3; 7] in men and 4 [[4; 11] in women (p = 0.25). Physical activity of 57.6 % in students corresponded to a moderate level. Healthy students were more likely to exhibit higher physical activity than individuals with FD and/or IBS symptoms, 56.5 and 31.9 %, respectively (p = 0.04). The level of wellbeing and severity of FD and/or IBS symptoms correlated negatively (r = –0.28, p = 0.01). Wellbeing and mood correlated directly with physical activity, r = 0.33, p = 0.001 and r = 0.27, respectively (p = 0.01).Conclusions. 1. Symptoms of FD and/or IBS occur widely among students and equally in men and women. Functional disorders of the gastrointestinal tract of mild to moderate severity occur in 23.9 % of students, with borderline symptoms registered with every second individual. 2. Healthy students significantly more often exhibited higher physical activity compared to individuals with FD and/or IBS symptoms of varying severity in the ratios of 56.5 and 31.9 % (p = 0.04). 3. Severity of FD and/or IBS in students negatively correlates with the wellbeing component of quality of life (r = –0.28, p = 0.01).